Ericoid mycorrhizal fungi as biostimulants for improving propagation and production of ericaceous plants - Wei, Xiangying; Zhang, Wenbing; Zulfiqar, Faisal; Zhang, Chunying; Chen, Jianjun (Frontiers in Plant Science, 2022)
The mutualistic relationship between mycorrhizal fungi and plant roots is a widespread terrestrial symbiosis. The symbiosis enables plants to better adapt to adverse soil conditions, enhances plant tolerance to abiotic and biotic stresses, and improves plant establishment and growth. Thus, mycorrhizal fungi are considered biostimulants. Among the four most common types of mycorrhizae, arbuscular mycorrhiza (AM) and ectomycorrhiza (EcM) have been more intensively studied than ericoid mycorrhiza (ErM) and orchidaceous mycorrhiza (OrM). ErM fungi can form symbiotic relationships with plants in the family Ericaceae. Economically important plants in this family include blueberry, bilberry, cranberry, and rhododendron. ErM fungi are versatile as they are both saprotrophic and biotrophic. Increasing reports have shown that they can degrade soil organic matter, resulting in the bioavailability of nutrients for plants and microbes. ErM fungi can synthesize hormones to improve fungal establishment and plant root initiation and growth. ErM colonization enables plants to effective acquisition of mineral nutrients. Colonized plants are able to tolerate different abiotic stresses, including drought, heavy metals, and soil salinity as well as biotic stresses, such as pathogen infections. This article is intended to briefly introduce ErM fungi and document their beneficial effects on ericaceous plants. It is anticipated that the exploration of this special group of fungi will further improve our understanding of their value of symbiosis to ericaceous plants and ultimately result in the application of valuable species or strains for improving the establishment and growth of ericaceous plants.